Undergraduate students’ use of shadow libraries as counter-enclosure of knowledge - Stanislaus Axel Paskalis; Alfredo Putrawidjoyo (Berkala Ilmu Perpustakaan dan Informasi, 2022)
Introduction. University students rely on heavily on academic literature, however, paywalls frequently stifle its access. To circumvent this limitation, they use shadow libraries, an unofficial archive of academic resources freely available online. We investigated how Universitas Gadjah Mada students use shadow libraries to mitigate the lack of access their institutions provide. Data collection methods. We collected data using an online survey involving 398 Universitas Gadjah Mada students to gather descriptive statistical data on the usage of shadow libraries and a literature study. Data analysis. We analyzed quantitative data with statistics processing software (Stata) and coded the open-ended qualitative responses. Results and Discussion. Students use shadow libraries because shadow libraries are more accessible and offer more access to literature than university library. They use shadow libraries despite their ambivalence due to shadow libraries’ legality. Moreover, some students also support shadow libraries, using them as part of an active effort to counter the enclosure of scholarly goods. Conclusion. Our findings show that shadow libraries have used a main alternative platform to access collections that are not available at the university library.